Kualitas Kimia Air Sumur di Perum Pondok Baru Permai Desa Bulak Rejo Kecamatan Sukoharjo Kabupaten Sukoharjo, Tahun 2015 - Tri Puji Kurniawan (Poltekkes Kemenkes Yogyakarta, 2017)
The standard thresholds for drinking water and clean water for domestic needs are regulated by The Decree of Minister of Health No. 492/Menkes/Per/IV/2010. The condition of water quality in Pondok Baru Permai Dwelling Complex at Bulak Rejo of Sukoharjo regency is poor. Physically, the water is having putrid odor, turbid and leaving yellowish and brownish color both in the wa-ter itself and also on bathrooms’ walls. Those indicate that the water contains Fe that exceeding the threshold. The research was an analytical observational study with cross sectional design. The data collected were primary quantitative ones as the measurement results of physical and chemical parameters of the water that consisted of: color, TDS, iron, total hardness, chloride, manganese, nitrite, pH, and sulphate. The measurements were conducted at the Environmental Health Laboratory of Sukoharjo Regency. Twenty artesian wells in the study location were se-lected by total sampling technique. The variables under study were environmental factors, i.e. distance from well to pollutant source, number of pollutant source for each well, well’s physical condition and type, and well’s water quality. Bivariate analysis was conducted by using Chi-Square test. The results show that most of the existing artesian wells have fulfilled the requisite for clean water source. However, one well is identified as under standard for drinking and clean water source because containing Fe, and five wells have Mn level that exceeding the thre-sholds for both drinking and clean water. Distance to pollutant, number of pollutant, well’s phy-sical condition and type correlate significantly with color, manganese level, pH and organic sub-stance of the wells.